Pengaruh Celebrity endorser dan Beauty vlogger terhadap Minat Beli Kosmetik Skintific - Dwi Sashianty; Diandra, Didip (JURNAL MANAJEMEN MOTIVASI, 2026)
The rise of social media has transformed how consumers seek information, particularly in the competitive beauty industry. Public figures like celebrity endorsers and beauty vloggers now play a key role in shaping perceptions and purchase intention, especially for popular skincare brands like Skintific. This study analyzes their influence using a quantitative descriptive method and purposive sampling of 150 respondents via Google Form. Data were analyzed using SmartPLS 4.1.0.0. Results show both variables have a positive, significant impact on purchase intention, with beauty vloggers being the most dominant. An R-square of 0.752 confirms their strong explanatory power on consumer behavior.